An Evaluation of the Effectiveness of a Combined Emotionally Focused Couple Therapy and Compassion Therapy in Improving the Quality of Marital Life and Dimensions of Couple Attachment - Khajeh, Amir Hesam; Farhadi, Hadi; Aghaei, Asghar (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to investigate the effectiveness of combined emotionally focused couple therapy and compassion therapy in improving the quality of marital life and dimensions of attachment of couples who visited counseling centers in Isfahan. Methods: The present study had a one-case experimental design and was conducted in 2019. The statistical population consisted of all couples who visited psychological centers and clinics in Isfahan. Sampling was performed on all couples who visited centers and clinics of Isfahan in winter 2019 for marital problems, and three couples were selected using the convenience method according to the inclusion and exclusion criteria. After initial sampling, three couples were included in the combined group of emotionally focused therapy and compassion therapy. The Marital Quality of Life Questionnaire (Marital Relationships) and the Collins and Read adult attachment Scale were used to collect data. The participants underwent combined emotionally focused couple therapy and compassion therapy in a session per week (12 sessions). Data were analyzed using the visual mapping, reliable change index, and recovery percentage formula. Results: Data analysis indicated the effectiveness of therapy in couples who were underwent combined emotionally focused couple therapy and compassionate therapy. Conclusion: The combination of emotionally focused couple therapy and compassion therapy affected the quality of marital life and dimensions of couple attachment, and thus the approach can be utilized to improve relationships and reduce divorce in society.